Loco-regional treatment of HCC: current status. Issue 8 (August 2017) - Crocetti, L.; Bargellini, I.; Cioni, R.
Abstract : Hepatocellular carcinoma (HCC) represents one of the few cancers for which locoregional treatments are recognised as being able to cure and/or prolong survival and are included in international guidelines. This is due to the unique nature of HCC, in most cases occurring in patients with underlying virus- or alcohol-related cirrhosis. The treatment choice in patients with HCC is therefore driven not only by tumour staging, as in the great majority of cancers, but also by careful evaluation of liver function and physical status. Another specific feature of HCC is that it is the only tumour that can be cured by organ transplantation, with the aim of treating both the cancer and underlying liver disease. These characteristics configure a complex scenario and prompt the need for close cooperation among interventional oncologists, surgeons, hepatologists, and anaesthesiologists. In patients with limited hepatic disease, preserved hepatic function and good performance status, categorised as very early and early-stage HCC according to the Barcelona Clinic Liver Cancer (BCLC) classification, image-guided tumour ablation is included among the curative treatments. More than half of patients with HCC are, however, diagnosed late, despite the widespread implementation of surveillance programmes, when curative treatments cannot be applied. For patients presenting with multinodular HCC and relatively preserved liver function, absence of cancer-related symptoms, and no evidence of vascular invasion or extrahepatic spread transcatheter arterial chemoembolisation (TACE) is the current standard of care. Although anti-tumour activity and promising survival results has been reported in cohorts of patients with advanced HCC treated with radio-embolisation, systemic treatment with the multi-kinase inhibitor, sorafenib, is still recommended for patients at this stage. In this article, current treatment strategies for HCC according to tumour stage are discussed, underlining the latest advances in the literature and technical developments.